2021
DOI: 10.3390/ijms22084192
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Profiling of Cucumber (Cucumis sativus L.) Early Response to Pseudomonas syringae pv. lachrymans

Abstract: Bacterial angular leaf spot disease (ALS) caused by Pseudomonas syringae pv. lachrymans (Psl) is one of the biological factors limiting cucumber open-field production. The goal of this study was to characterize cytological and transcriptomic response of cucumber to this pathogen. Plants of two inbred lines, B10 (susceptible) and Gy14 (resistant), were grown, and leaves were inoculated with highly virulent Psl strain 814/98 under growth chamber conditions. Microscopic and transcriptional evaluations were perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 67 publications
0
5
0
Order By: Relevance
“…Both the cytological and transcriptomic responses of cucumber to Pseudomonas syringae pv. lachrymans (Psl) were characterized to elucidate the mechanism underlying cucumber resistance to bacterial angular leaf spot disease [28].…”
Section: Transcriptome Research Of Cucumbermentioning
confidence: 99%
“…Both the cytological and transcriptomic responses of cucumber to Pseudomonas syringae pv. lachrymans (Psl) were characterized to elucidate the mechanism underlying cucumber resistance to bacterial angular leaf spot disease [28].…”
Section: Transcriptome Research Of Cucumbermentioning
confidence: 99%
“…For instance, cucumber bacterial angular leaf spot disease (ALS) is caused by Pseudomonas syringae pv. lachrymans ( Psl ), which mainly infects the leaves and results in limited vein and necrotic tissues [ 37 , 38 ]. In addition, cucumber fusarium wilt, one of the major fungal diseases, is a soil-borne disease caused by Fusarium oxysporum f. sp.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have found two major quantitative trait loci psl5.1 and psl5.2 related to disease severity through genetic mapping of the Psl locus, which may be suitable to support selection for angular leaf spot resistance (Słomnicka et al, 2018). Słomnicka et al (2021) found reactive oxygen species (ROS) in managing early defense response of cucumber to Psl , and some genes involved in host‐specific response to the highly virulent Psl strain. Pazarlar et al (2021) reported that exogenous pipecolic acid induced systemic acquired resistance (SAR) in cucumber against Psl .…”
Section: Introductionmentioning
confidence: 99%